Morphological, textural and structural features of chromitite deposits of Main ore field of Kempirsay massif (South Urals, Kazakhstan) - D. E. Saveliev; D. K. Makatov; V. S. Portnov; R. A. Gataullin (Georesursy, 2024)
In the paper data of morphology, textural and structural features of chromitites from deposits of southeast part of Kempirsay massif (South Urals, Kazakhstan) are summarized. It is showed that formation of unique chromium deposits is closely related with formation processes of wall dunite-harzburgite association and that chromitite localization occur abidingly in olivine monomineralic rock – dunite. Superimposed low-T processes altered primary mineralogical composition of wall peridotites completely but these affected weakly their structure on the micro and macro scale. Mesh serpentine replaced olivine and pyroxene grains but pseudomorphosis of both are survive. Addition, significant displacements of mineral aggregates in the massive peridotite blocks are not observed and it allow to study textural and structural characteristic of chromitites and primary wall ultramafic rocks. We have found some major features of building of ore-bearing associations as follow: (i) increasing chromite grain size according to increasing concentration of chromite, (ii) widespread of deformational structures – ore folding and boudinage, extrusion of solid dunite into massive chromitite, break of ore veinlets. We have performed retrospective analysis of papers about Kempirsay chromitite which in present day are not available for wide readers. Based on this analysis and our observations, we propose a modified dynamic model of chromitite formation as result rheomorphic differentiation of upper mantle matter during its upwelling from deep zone of rift structure with later transformation in the upper mantle of fore-arc setting.